Symbol Attributes in the Allegorical Roles of Animals in Kalila wa Dimna - Mohammadzadeh, Maryam; Mahmoudi, Masoume (Journal of History Culture and Art Research, 2017)
Kalila wa Dimna is one of the allegorical works in Persian language in which the author discussed the critical issues involving moral, political, social beliefs with regard to the government and what was inexpressible by a normal way have been indirectly expressed in the form of stories by animal characters. This article by the means of descriptive and analytical methods, studies these allegories, it has analyzed allegorical attributes animal symbols in Kalila wa Dimna and suggests that Nasrallah Monshi in order to express his ideas about political issues, has selected fable narrative allegory.